Acute Appendicitis in Patients with Acute Leukemia - Kim, Ki Up (Korean J Intern Med, 1993)
The decision to operate for abdominal pain in patients with leukopenia can be exceedingly difficult. Surgical exploration may be the only effective way to differentiate acute appendicitis from other causes, but it involves considerable risk of infectious complications due to immunesuppression. Leukemic patients, who presented significant RLQ pain, had been indicated for operation, despite having advanced disease or having had received chemotherapy or steroids. Four adult leukemia patients, complicated by acute appendictis, were reviewed. Two patients were in induction chemotherapy, one receiving salvage chemotheapy due to relapse and the other was in conservative treatment. Two patients were acute myelocytic leukemia (AML), one had acute lymphocytic leukemia (ALL), and the other had aleukemic leukemia. All patients underwent appendectomy and recovered without complication. Our experience supports the theory that the surgical management of appendicitis in acute leukemia is the most effective way, in spite of leukopenia.